KULTUR POLIEMBRIONI BIJI DUKU (Lansium domesticum. CORR.) PADA MEDIA MS DAN WPM DENGAN PENAMBAHAN AIR KELAPA - Prihatini, Retno; Yahya, Sudirman; Purwito, Agus (Sainstek : Jurnal Sains dan Teknologi, 2010)
The study on growth respons of Lansium domesticum  poliembryoni seed on MS and WPM media with added by coconut water had been carried out from Maret up to Mei 2006. This experiment had been done in Tissue Culture Laboratory, Agronomy-Holticulture Depatment, Agronomy Faculty, Institute Pertanian Bogor, using  two factorial of Completely Randomized Design with  nine treatments, and ten replications. The first factor treatment were  MS, ½ MS and WPM media, and the 2nd  factor were 0, 15 and 20% coconut water. The result showed that the emergence time of the first adventitious shoot were beginning on 26,5 days after planting, with one until four numerous of shoots, on MS, ½ MS, WPM media with added  until 20% coconut water. There were only 50-70% shoot formed on 8 weeks after planting. With 20% coconut water suplemented on MS culture media showed that the height of shoots were significant than controle.Key words: Lansium domesticum, coconut water, polyembryonic seed, culture media.